Review of mixture formation unit for CNG motorcycle - Mohsin, R.; Yaacob, Z.; Y., Chang (Faculty of Chemical Engineering & Natural Resources, 2008)

(untitled)
The poor mixing homogeneity and air-fuel ratio controllability of the former mixture formation units for a CNG motorcycle are deemed to be the culprits of its lethal exhaust emissions and poor engine performance, In this research, the fuel system of a CNG powered motorcycle, focusing on the mixture formation unit was reviewed. Owing to the significant benefits of the single-point-injection-type (SPIT) system over the mixer-type (MT) system, attempts to develop a mixer with the SPIT system, i.e. Throttle Body Injection Mixer (TBIM), was conducted through Computational Fluid Dynamics (CFD) modelling. CFD results revealed a significant improvement of mixing homogeneity in TBIM.